Effect of fins and nanoparticles in the discharge performance of PCM thermal storage system with a multi pass finned tube heat exchange. (25th July 2022) - Pássaro, João; Rebola, A.; Coelho, L.; Conde, J.; Evangelakis, G.A.; Prouskas, C.; Papageorgiou, D.G.; Zisopoulou, A.; Lagaris, I.E.
Abstract: This work studies the heat exchange process of a latent heat thermal energy storage (LHTES) system equipped with a compact finned tubes heat exchanger (HE) as this is one of the most important aspects of the storage system, the capacity for effectively delivering its stored energy. This work fills in a literature gap for 3D, transient heat transport fluid (HTF) flow models concerning storage systems with phase change materials (PCMs) with fins and nanoparticles allowing for an evaluation on the quality of heat delivered by the system. Numerical simulations, for full turbulent conditions of the HTF flow, were developed to access the influence of the fin pitch and the PCM thermal properties in the performance of the energy discharge process. Samples of commercial paraffin-wax A53 doped with graphene based nanoplatelets were tested and characterised. Different types of nanoplatelets were employed in the range of 0.5% to 6% weight. Measured data of the thermal conductivity, specific heat and fusion latent heat are presented. The simulations were developed for three fin pitch values 5, 10 and 20 mm and for 1%wt and 6%wt nanoparticles loads. The effect of fins and combination of fins and nanoparticles in the outlet temperature and liquid fraction distribution inside the LHTES unit during the discharge process in a 3D full scale model was analysed. The system performance was evaluated based of off the outlet temperature of HTF to ascertain both the quantity and quality of the heat provided. The results show that the PCM thermal conductivity is significantly enhanced by the addition of graphene nanoparticles with a high aspect ratio. The addition of only 1%wt doubled the solid phase PCM thermal conductivity and for a 6%wt load the thermal conductivity increased by a factor of 3.5. Meanwhile, specific and latent heat values of the samples are relatively unaffected. The numerical results further show that applying thin fins is an effective approach to enhance LHTES systems discharge performance. Increasing the fin number significantly enhances the heat transfer rate and the HTF discharge temperature during solidification and has a positive impact in the useful discharge heat capacity, providing better quality heat. Combining fins and nanoparticles improves the discharge process, nevertheless the role of nanoparticles becomes secondary as the fins number increases. The results demonstrate that standardised compact finned heat exchangers ubiquitously used in the HVAC industry can successfully overcome the low thermal conductivity of common PCMs without compromising the useful heat discharge capacity or resorting to nanoparticles decreasing the discharge time between 60 and 77% with adequate fin number. Highlights: Samples of paraffin-wax with graphene nanoplatelets employed and characterised. The paraffin thermal conductivity improved via nanoparticles with a high aspect ratio. The paraffin specific and latent heat marginally affected by the nanoparticles. 3D simulations, for full turbulent conditions of the heat transport fluid (HTF) flow. Results showed employing HE fins with proper fin pitch replaces need of particles.